Individualized Therapy for Complicated Cranial Defect: A Case Report - Yu, Nanze; Liu, Zhifei; Zhang, Hailin; Wang, Xiaojun (Acta Biomedica Atenei Parmensis, 2013)
Despite the considerable advances in plastic surgery in recent years, complicated large cranial defects remain challenging clinical entities with no clear management algorithms, especially in the pediatric age group.We present a 9-year old boy who underwent a hemispherectomy for Rasmussen encephalitis. Functional and cosmetic outcomes are considered during the procedure.